Concurrent chemoradiotherapy for locally advanced squamous cell carcinoma of the cervix in a uterus didelphys with vaginal septum - Yuko Kaneyasu; Iemasa Koh; Hisaya Fujiwara; Eiji Hirata; Yoshiki Kudo; Koji Arihiro; Norio Miharu; Tomio Nakagawa; Ippei Takahashi; Yuki Takeuchi; Nobuki Imano; Ikuno Nishibuchi; et al. (Journal of Contemporary Brachytherapy, 2019)
In November 2011, a 61-year-old woman was diagnosed with squamous cell carcinoma (SCC) of the cervix in a uterus didelphys with vaginal septum. The patient was diagnosed with Fédération Internationale de Gynécologie et d’Obstétrique (FIGO) stage IIB because of infiltration to the left parametrium without infiltration to the pelvic wall. The patient was treated with external-beam radiotherapy (EBRT) and brachytherapy (BT), using concomitant chemotherapy with cisplatin. A total of 50 Gy were delivered (2 Gy/fraction/day) to the pelvis, with a central shield after 40 Gy. The patient was treated four times with BT (6 Gy × 4 fractions), with tandem and ovoid applicators inserted once to the left side; tandem to the left side and ovoid bilaterally were inserted twice; and tandem to the right side and ovoid bilaterally were inserted once. Six years and 8 months after the start of treatment, the patient had had no relapse or severe late adverse effects. For accurate diagnosis and optimal treatment of the uterus didelphys, careful interview and pelvic examination at initial diagnosis of a patient are very important.